Postoperative changes in neutrophil-to-lymphocyte ratio and platelet count: A simple prognostic predictor for adult-to-adult living donor liver transplantation - Hironori Hayashi; Hiroyuki Takamura; Yoshinao Ohbatake; Shinichi Nakanuma; Hidehiro Tajima; Sachio Fushida; Ichiro Onishi; Takashi Tani; Koichi Shimizu; Tetsuo Ohta (Asian Journal of Surgery, 2018)
Summary: Background/Objective: The neutrophil-to-lymphocyte ratio (NLR) is a simple index that represents systemic inflammatory change. The number of platelets is also known to reflect both post-transplant graft regeneration and dysfunction. Thus, we aimed to investigate the usefulness of NLR and platelet number in predicting the clinical course after adult-to-adult living donor liver transplantation (AA-LDLT) in the acute postoperative period in recipients. Methods: Between January 1999 and December 2013, 61 patients underwent their first AA-LDLT at our institute. We retrospectively analyzed their clinical data, including NLR and number of platelets, until postoperative day 14, and evaluated their ability to predict prognosis after AA-LDLT. Results: The optimal cutoff values of postoperative maximum NLR and maximum platelets to predict prognosis were 50 and 80 × 103/μL, respectively. The 1- and 5-year survival rates were 87.5% and 79.1% in the normal maximum NLR group, respectively, and 46.2% for both in the high maximum NLR group (p = 0.0033). The 1- and 5-year survival rates, respectively, were 90.9% and 84.1% in the high maximum platelets group and 47.1% and 41.2% in the low maximum platelets group (p < 0.0001). In multivariate analysis, maximum NLR ≥ 50 and maximum platelets < 80 × 103/μL were independently associated with 1-year mortality. Conclusion: A high NLR and a low platelet count during acute postoperative period might correlate with poor prognosis after AA-LDLT. Keywords: complete blood count, neutropenia, postoperative complications, thrombocytopenia